NFAT1 Regulates Ly6Chi Monocyte Recruitment to the CNS and Plays an Essential Role in Resistance to Toxoplasma gondii Infection - Benevides, Luciana; Saltarelli, Verônica M.; Pioto, Franciele; Sacramento, Laís A.; Dias, Murilo S.; Rodríguez, Gretel R.; Viola, João P. B.; Carregaro, Vanessa; Silva, João S. (Frontiers in Immunology, 2019)
Monocytes play key roles in the maintenance of homeostasis and in the control of the infection. Monocytes are recruited from the bone marrow to inflammatory sites and are essential for antimicrobial activity to limit tissue damage and promote adaptive T cell responses. Here, we investigated the role of NFAT1 in the regulation of Ly6Chi inflammatory monocyte recruitment to the CNS upon T. gondii infection. We show that NFAT-1-deficient monocytes are unable to migrate to the CNS of T. gondii-infected mice. Moreover, NFAT1-/- mice are highly susceptible to chronic T. gondii infection due to a failure to control parasite replication in the CNS. The inhibition of Ly6Chi inflammatory monocyte recruitment to the CNS severely blocked CXCL10 production and consequently the migration of IFN-γ-producing CD4+ T cells. Moreover, the transfer of Ly6Chi monocytes to infected NFAT1-/- mice favored CD4+ T cell migration to the CNS and resulted in the inhibition of parasite replication and host defence. Together, these results demonstrated for the first time the contribution of NFAT1 to the regulation of Ly6Chi monocyte recruitment to the CNS and to resistance during chronic T. gondii infection.